Doença(s) e mortalidade de escravos em Victoria, província do Espírito Santo (1849 - 1880) - Felipe, José Mauriene Araújo (2019)
It investigates rates of illness and mortality incidences of slave population living in Vitoria, capital of the province of Espírito Santo, along the period from 1849 to 1880. To enter this local and unknown universe, initially it was necessary to develop an introductory study on the slavery's multiple faces in Espírito Santo, starting by the narration of some everyday biases, permeating life conditions involving heavy lifting, revolts, punishments, leaks, prisons, the illness in prisons, even the extreme act of suicide. To this end, data collection on such particularities, aimed itself to elaboration of statistical maps that allow knowledge of care provided to the slave health, types of relationships between lord and captives, as well as allow to have more idea of the causes which forced captives to commit suicide in the form of ultimatum. With the results obtained from these first elements, studies were guided to know the disease incidence and mortality rates of slaves in the Vitoria of the second half of the 19th century. It was aimed to facilitate data collection around specific topics such as: urban slave life, their mobility, types of work, housing, food and hygiene. Confronting these data, it might have better perception about living conditions, health related to the types of illnesses acquired and, when it was an extreme situation, to death. The final results point out to high levels of slaves death, and also for the high levels of captives' children mortality in the Vitoria of the abovementioned period. For the development of this research, the following sources were taken: book of obits, reports and speeches of provincial presidents, providers of public health reports, newspapers, memoirs and books produced in the course of the 19th century. The theoretical intake had the basement of recent studies directed to the interfacial dialogue between history and health sciences. In the context of historical demography, it was elected the methodology of demographic system of slave populations. With regard to this study, the goal is to contribute for the production of research on the history of health and disease in general; lead studies on slavery and, first of all, encourage the research directed to health, disease and mortality of slaves in Espírito Santo of colonial and provincial periods.